The Integration between Islamic Science and Social Sciences in Facing the Globalization: Future Outlook | التكامل المعرفي الإسلامي في العلوم الاجتماعية في مواجهة الكوكبية: نظرة مستقبلية - Syakir Rizq Taqiyuddin (Al-Zahra : Journal for Islamic and Arabic Studies, 2018)
The discussion of integration between Islamic science and other sciences is one of the most important issues in the contemporary era, the third millennium, so the discourse should be conducted scientifically and systematically. This article aimed to highlight the concept of integration of knowledge generally, and reveal some of its formats. therefore, the writer also recommends a number of ways to realize the integration of knowledge in Islamic Educational Institution at all levels, through 1) Cognitive integration between Shari'a sciences and humanities in postgraduate studies (master's and doctoral) and scientific research. 2) Encouraging joint scientific research between different disciplines and within the same specialization, through the establishment of centres, laboratories and research teams that deal mainly with the concept and methodology of knowledge integration between science, etc.